Employing cash waqf in financing micro, small and medium enterprises for sustainable poverty alleviation: grounded theory approach - Sanyinna, Abubakar Yusuf; Omar, Hydzulkifli Hashim (2019)
Waqf is the most effective way of expressing philanthropy for sustaining the welfare of the poor. It is a special mechanism through which constructive wealth is transferred from private ownership to public utility for servicing all sectors of life. So long as governments alone cannot cater for the basic needs of their peoples, philanthropic initiatives should be systematically exploited to tackle the menace of poverty. As an act of worship, waqf proves to be a prominent institution that caters for not only the poor but the entire community. About 75% of business opportunities in developing countries are proved to be provided by micro-, small- and medium-enterprises (MSMEs). Unfortunately, these vital job-providers are mostly underfinanced thereby leaving wide vacuums to be filled by ravaging poverty. This paper perceives the poor to be either active or inactive. The active poor are those who are physically and mentally capable of running dependable enterprises but are constrained by lack of, or inadequate, capital. The inactive poor, on the other hand, are those living in poverty while they are physically and/or mentally impaired. By adopting the grounded theory approach of qualitative research method, the researchers explore how poverty alleviation could be sustained through utilizing cash waqf to develop the earning potentials of the active poor for self-reliance and to provide decent social security services to the inactive poor.